Dampak Kecanduan Game Online Terhadap Siswa SMK PGRI Kabupaten Kepulauan Aru - Anggrek Kamsy; Herry R Lekatompessy; Hellen Pattiruhu (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2021)
Abstrack:Â This research is directed to find the factors that cause the rise of online games among students, especially at the high school level, and its impact on their attitudes and behavior both at school and at home. The data collection process used a descriptive qualitative method with a purposive sampling technique to determine informants. Through observation, interviews, and documentation techniques, data and information in the field were processed, analyzed, interpreted, and then concluded for 30 students, involving guidance, counseling, homeroom teachers, and school principals at SMK PGRI Dobo, Aru Islands Regency. Based on the results of the study, it was found that online games had a psychological impact on students so that it influenced their attitudes and behavior in communicating, acting, socializing, and in the learning process in class. There are efforts made by the school in overcoming the impact of online games on student behavior through providing guidance, advice, sanctions, and establishing good coordination with parents. Collaboration and coaching collaboration between schools and parents is a model that is considered capable of solving problems faced by students both now and in the future.Â Keywords: Impact of Addiction,Â